Faktor-Faktor yang Berhubungan dengan Kesediaan Menjadi Akseptor KB Pasca Persalinan di RSUD Deli Serdang Lubuk Pakam Tahun 2019 - Julina Br Sembiring; Suyanti Suwardi; Herna Juliati Saragih (Universitas Batanghari Jambi, 2020)
Increasing the population is one of the big problems for developing countries. Indonesia is the country with the largest population after China, India and the United States. To get quality reproductive health services, each partner of childbearing age must have equal access to contraception and services that can save his life, one of which is a postpartum family planning program. Willing to become a postpartum family planning acceptor is an option for every couple of childbearing age. Many factors are related to the willingness to become postpartum family planning acceptors. Method this research is analytical cross-sectional, which is measuring or observing all dependent variables (willingness to become post-birth control acceptors) with independent variables (knowledge, attitude, husband support and officer role). The result level of knowledge (p value 0,028 <0,05), attitude (value p value 0.01 <0.05), husband's support (p value 0.00 <0.05), and the role of health workers (p value 0.00 <0.05). is related to willingness to become a postpartum acceptor while education is not a willingness factor to become a postpartum family planning acceptor (p value 0.327> 0.05).